Fc-binding nanodisc restores antiviral efficacy of antibodies with reduced neutralizing effects against evolving SARS-CoV-2 variants - Jaehyeon Hwang; Soyun Choi; Beom Kyu Kim; Sumin Son; Jeong Hyeon Yoon; Kyung Won Kim; Wonbeom Park; Hyunjoo Choo; Suhyun Kim; Soomin Kim; Seokhyeon Yu; Sangwon Jung; et al. (Journal of Nanobiotechnology)
Abstract Passive antibody therapies, typically administered via parenteral routes, have played a crucial role in the initial response to the COVID-19 pandemic. However, the ongoing evolution of SARS-CoV-2 has revealed significant limitations of this approach, primarily due to mutational escape and the inadequate delivery of antibodies to the upper respiratory tract. To overcome these challenges, we propose a novel prophylactic strategy involving the intranasal delivery of an antibody in combination with an Fc-binding nanodisc. This nanodisc, engineered to specifically bind to the Fc regions of IgG antibodies, served two key functions: extending the antibody's half-life in the larynx and trachea, and enhancing its neutralization efficacy. Notably, Sotrovimab, an FDA-approved monoclonal antibody that has experienced a significant decline in neutralizing potency due to viral evolution, exhibited robust antiviral activity when complexed with the nanodisc against all tested Omicron variants. Furthermore, the Fc-binding nanodisc significantly boosted the antiviral efficacy of the soluble angiotensin-converting enzyme 2 (sACE2) Fc fusion protein, which possesses broad but modest antiviral activity. In ACE2 transgenic mice, the Fc-binding nanodisc protected better than sACE2-Fc alone with two more log reduction in lung viral titer. Therefore, the intranasal Fc-binding nanodisc offers a promising and powerful approach to counteract the diminished antiviral activity of neutralizing antibodies caused by mutational escape, effectively restoring antiviral efficacy against various evolving SARS-CoV-2 variants.